Equações de Navier-Stokes: Uma Perspectiva Numérica. - Pereira, Charles de Aguiar (2021)
In this present work, we will start with a theoretical study of Navier-Stokes equations, followed by three topics in computational physics for fluid resolution: Discontinuous Galerkin, Finite Volumes and Lattice-Boltzmann. We approach fluid model problems such as Kelvin-Helmholtz Instability and Rayleigh-Taylor Instability and the following addresses a problem of plasma prominences on the solar surface related to the study of magnetohydrodynamics.